Edukasi Pemanfaatan Pisang Kepok sebagai Media Tumbuh Bakteri dan Aplikasi Fisika dalam Proses Pengolahan Tepung Pisang di SMA Negeri 7 Medan - Lubis, Retnita Ernayani; Sapitri, Alfi; Diansari Marbun, Eva; Arisetya, Dian (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2025)
This community service activity aims to improve students' scientific literacy through education on the use of kepok bananas as an alternative medium for bacterial growth and the application of physics concepts in the process of processing banana flour. The program was implemented at SMA Negeri 7 Medan, which has limited science laboratory facilities, so that learning is still predominantly theoretical. The activity was designed through four main stages: initial survey, socialization, training, and mentoring. Students were guided to recognize the starch content in bananas as an energy source for microorganisms and to understand the principle of heat transfer in drying bananas. Implementation was carried out through direct practice of making banana flour and bacterial culture media based on local materials. Evaluation of the results showed a significant increase in student understanding, with more than 80% of students successfully making effective growth media marked by the formation of even bacterial colonies. In addition, 92% of students stated that this activity increased their understanding of science in an applicable and enjoyable way. This activity also opens up opportunities for cross-disciplinary integration (biology and physics) and the potential for entrepreneurship based on banana processing. The entire program proves that science learning based on local materials and direct practice can be an effective strategy to improve students' scientific skills and learning independence in high schools.